Viabilidade do ecoturismo científico com onça-pintada na reserva Mamirauá, Amazônia - Nassar, Pedro Meloni (Instituto Nacional de Pesquisas da Amazônia - INPA, 2013)
The jaguar is considered endangered throughout most of its range and efforts for the conservation of the species are not very effective to protect it. Ecotourism, defined as an activity that promotes improvement of quality of life and the creation of environmental awareness of the populations involved, may be an important strategy for the conservation of some species, including the jaguar (Panthera onca). The key points of ecotourism are minimal impacts to the environment and to the local culture, while generating income for local communities. In this study was assessed whether ecotourism practiced in Sustainable Development Reserve (SDR) Mamirauá had any effect on the perception of local people towards conservation of the jaguar and the creation of a package of scientific ecotourism with the jaguar. It was also analyzed the viability of scientific ecotourism with jaguar as a strategy for conservation of the species. Were interviewed 144 residents of 12 communities, six which participate of the SDR Mamirauá Ecotourism Program and six which do not participate. There was no clear difference between the two groups of communities towards conservation of the jaguar and both groups supported the establishment of the scientific ecotourism package with jaguar. The economic viability was performed using a spreadsheet cash flow, accounting for all fixed and variable costs, investments, depreciation and revenues. Were analyzed 18 scenarios of daily values and different number of tourists. The Net Present Value (NPV) of each scenario was calculated. The NPV indicates the feasibility of each scenario. The market feasibility was done through questionnaires sent via the Internet, for two groups called technical-scientific (academic researchers, working in the area of conservation and ecology, managers of national protected areas , veterinarians who work with wild animals and NGOs) and group of ecotourism (ecotourists, nature photographers, tourism researchers, tour guides and tour operators). Both groups were in favor of the proposal. The features that the scientific ecotourism package should provide were quality information, supporting environmental education and research, and financial returns to local communities. The most preferred activities were tracking telemetry and search for evidence of the jaguar. The impacts of the scientific ecotourism considered most relevant were the possibility to the jaguar get used to human presence and make the animal abandon its territory. The daily values of between R$ 350.00 and R$ 500.00 were those considered most fair. The NPV analysis indicated that eight scenarios were feasible. The results of this study indicate that there is an acceptance of the proposal by the market and the local communities and the SDR Mamirauá. There are positives scenarios, indicating minimum values of visitors per year and the minimum daily values to be charged. Thus, the scientific ecotourism with jaguar is capable of maintaining the initial 10 years, generating economic benefits for local communities and the jaguar research.
Keywords: Ecoturismo; RDS Mamirauá; Onça-pintada; Conservação